Direct observation of oxygen-vacancy formation and structural changes in Bi2WO6 nanoflakes induced by electron irradiation - Shi, Hong-long; Zou, Bin; Li, Zi-an; Luo, Min-ting; Wang, Wen-zhong (Beilstein Journal of Nanotechnology, 2019)
The prominent role of oxygen vacancies in the photocatalytic performance of bismuth tungsten oxides is well recognized, while the underlying formation mechanisms remain poorly understood. Here, we use the transmission electron microscopy to investigate the formation of oxygen vacancies and the structural evolution of Bi2WO6 under in situ electron irradiation. Our experimental results reveal that under 200 keV electron irradiation, the breaking of relatively weak Bi–O bonds leads to the formation of oxygen vacancies in Bi2WO6. With prolonged electron irradiation, the reduced Bi cations tend to form Bi clusters on the nanoflake surfaces, and the oxygen atoms are released from the nanoflakes, while the W–O networks reconstruct to form WO3. A possible mechanism that accounts for the observed processes of Bi cluster formation and oxygen release under energetic electron irradiation is also discussed.
Keywords: bismuth tungsten oxide; electron diffraction; electron irradiation; nanoflakes; oxygen vacancies